2002
DOI: 10.1002/eat.10016
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of anorexia nervosa subtypes

Abstract: The findings on impulsivity, course, and outcome do not support the current subtyping system. The high crossover rate in our sample from ANR to ANBP suggests that ANR represents a phase in the course of AN rather than a distinct subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
175
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 27 publications
10
175
2
3
Order By: Relevance
“…Although research indicates that the overarching diagnosis of ''eating disorder'' is relatively stable, 3 several studies suggest that there is considerable longitudinal instability of the specific eating disorder diagnoses of AN, BN, and EDNOS in treatment samples, resulting from recovery, relapse, and crossover between and within the eating disorder diagnoses. 3,[4][5][6] The recovery rates for AN and BN were moderate to high at each of the follow-up assessments in Fichter and Quadflieg study, which is similar to the rates reported by Ben-Tovim et al, 7 who found that at 5-year follow-up, 56% of patients with AN, 74% of patients with BN, and 78% of patients with EDNOS no longer met criteria for any eating disorder diagnosis.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andsupporting
confidence: 74%
See 2 more Smart Citations
“…Although research indicates that the overarching diagnosis of ''eating disorder'' is relatively stable, 3 several studies suggest that there is considerable longitudinal instability of the specific eating disorder diagnoses of AN, BN, and EDNOS in treatment samples, resulting from recovery, relapse, and crossover between and within the eating disorder diagnoses. 3,[4][5][6] The recovery rates for AN and BN were moderate to high at each of the follow-up assessments in Fichter and Quadflieg study, which is similar to the rates reported by Ben-Tovim et al, 7 who found that at 5-year follow-up, 56% of patients with AN, 74% of patients with BN, and 78% of patients with EDNOS no longer met criteria for any eating disorder diagnosis.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andsupporting
confidence: 74%
“…Another study indicated that 40% of the patients with BN recovered over a 2-year follow-up 8 and 74% had recovered by 5-year follow-up. 6 Eddy et al 4 found that 46% of patients with restricting AN and 39% of patients with binge/ purge AN achieved recovery over a period of 8 years. Moreover, another prospective study of a treatment sample found that the average duration of AN was 10 years.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, recent studies, including prospective longitudinal studies, have failed to find significant evidence of differences between the binge purge and restricting subtypes of AN in comorbid psychopathology, recovery, relapse, or mortality rates. 8 In addition, most individuals with restricting AN are likely to report some binge-purge behaviors over time. 8 This evidence may suggest that AN binge-purge subtype represents a more severe or chronologically advanced form of AN, rather than a distinct diagnostic subtype.…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…Between 8% and 62% of individuals with an initial diagnosis of AN develop bulimic symptoms at some point during the course of their illness, [29][30][31][32][33][34][35][36][37] with the majority of crossovers occurring within the first 5 years. 29,30,32,37 Understanding Risk Factors for Anorexia Nervosa AN afflicts fewer than 1% of the population.…”
Section: Pubertal Developmentmentioning
confidence: 99%